A through bond energy transfer based ratiometric probe for fluorescent imaging of Sn2+ ions in living cells. Issue 46 (20th April 2016) - Adhikari, Susanta; Ghosh, Avijit; Guria, Subhajit; Sahana, Animesh
Abstract : A 4-(naphthalen-1-ylethynyl) aniline appended rhodamine based fluorescent chemosensor 'NAP-RD ' is synthesized which undergoes through bond energy transfer in the presence of Sn 2+ ions in mixed aqueous media. Abstract : A 4-(naphthalen-1-ylethynyl) aniline appended rhodamine based fluorescent chemosensor 'NAP-RD ' is synthesized which undergoes through bond energy transfer in the presence of Sn 2+ ions in mixed aqueous media.NAP-RD is an excellent colorimetric and fluorescence ratiometric probe which recognizes traces of Sn 2+ in real samples and a fluorescence indicator in living RAW264.7 cells. The new sensing probeNAP-RD shows higher sensitivity as well as faster response compared to the reported systems. The detection limit ofNAP-RD is 5 × 10 −9 M. DFT studies strongly support the experimental results.